Feasibility of N1-P2 habituation to differentiate loudness levels - Mai Mariam; Mustaffa, I.; Muzzammil, K. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/